Pore confinement effects and stabilization of carbon nitride oligomers in macroporous silica for photocatalytic hydrogen production. (September 2016) - Qiao, Sha; Mitchell, Robert W.; Coulson, Ben; Jowett, Danielle V.; Johnson, Benjamin R.G.; Brydson, Rik; Isaacs, Mark; Lee, Adam F.; Douthwaite, Richard E.
Abstract: An ordered macroporous host (mac-SiO2 ) has been used to prevent aggregation of layered photocatalysts based on carbon nitride. Using typical carbon nitride synthesis conditions, cyanamide was condensed at 550 °C in the presence and absence of mac-SiO2 . Condensation in the absence of mac-SiO2 results in materials with structural characteristics consistent with the carbon nitride, melon, accompanied by ca. 2 wt% carbonization. For mac-SiO2 supported materials, condensation occurs with greater carbonization (ca. 6 wt%). On addition of 3 wt% Pt cocatalyst photocatalytic hydrogen production under visible light is found to be up to 10 times greater for the supported composites. Time-resolved photoluminescence spectroscopy shows that excited state relaxation is more rapid for the mac-SiO2 supported materials suggesting faster electron-hole recombination and that supported carbon nitride does not exhibit improved charge separation. CO2 temperature programmed desorption indicates that enhanced photoactivity of supported carbon nitride is attributable to an increased surface area compared to bulk carbon nitride and an increase in the concentration of weakly basic catalytic sites, consistent with carbon nitride oligomers.